Effect of intrathecal Bupivacaine-Lidocaine combination on motor block and analgesia period - Sara El-Adawy; Azza Abd-El Alim; Manal El-Hamamsy (Faculty of Pharmacy, Cairo University, 2012)
Objective: To assess the effect of intrathecal Bupivacain-Lidocaine combination at different doses of Lidocaine (6 and 12 mg) on the onset and recovery of anesthesia. Methods: Ninety patients who were scheduled for elective lower abdominal surgery were randomly allocated into three equal groups: Group I; 30 patients received 1.5 mL hyperbaric 0.5% Bupivacaine + 0.6 mL saline. Group II; 30 patients received 1.5 mL hyperbaric 0.5% Bupivacaine + 0.6 mL 1% Lidocaine [6 mg] mixed. Group III; 30 patients received 1.5 mL hyperbaric 0.5% Bupivacaine + 0.6 mL 2% Lidocaine [12 mg]. Peak sensory block level, time to peak sensory block, times to two-segment, S2 regressions from peak sensory block, motor blocks at peak sensory block and total motor block duration, post anesthesia care unit stay time and analgesia time were measured. Results: The median height of peak sensory block in Group III was higher than in Group I or II. Times to two-segment and S2 regressions from peak sensory block, motor block duration and PACU time were significantly reduced in Group II compared to Group I and III. No patient required general anesthesia. No patients experienced postdural puncture headache or TNS. Conclusions: Lidocaine 1% (6 mg) mixed to spinal 1.5 mL hyperbaric 0.5% Bupivacaine (7.5 mg) can shorten the duration of Bupivacaine spinal anesthesia, provide more rapid recovery from the spinal anesthesia compared to the same dose of 0.5% Bupivacaine (7.5 mg) alone or the same dose of 0.5% Bupivacaine (7.5 mg) mixed with 0.6 mL 2% Lidocaine (12 mg).